Waldenstroms Macroglobulinemia- Diagnostic difficulties- a rare case report (Bangladesh Journal of Medical Science, 2019)
Waldenstrom’s macroglobulinemia(WM) is a B-cell neoplasm characterized by infiltration of the bone marrow by a lymphoplasmacytic infiltrate and an IgM monoclonal gammopathy. We report a rare case of a 72 year-old male who presented with fever, shortness of breath for one month. Examination revealed cervical and axillary lymphadenopathy with mild hepatomegaly. On evaluation, peripheral smear show significant rouleaux formation & bone marrow aspiration showed lymphoplasmacytic infiltration. Flow cytometry on bone marrow apirate suggestive of B cell neoplasm and serum protein electophoresis & Immunofixation study confirms diagnosis of waldenstroms macroglobulinemia. We report this case to emphasize diagnostic difficulties in diagnosis of waldenstorms macroglobulinemia and application of flow cytometry and immunofixation study for further confirmation and treatment.Bangladesh Journal of Medical Science Vol.18(3) 2019 p.656-659